The fate of small-mammal carrion is affected by carcass size and visual conspicuousness in a Neotropical rainforest - Romero, Andrea (THERYA, 2020)
Scavenging of carrion is essential to terrestrial ecosystems and can shape food webs and behavior. The prevalence and importance of scavenging has often been underestimated and overlooked in food web studies. Small-mammal carrion is even less studied and difficult to estimate, especially in the Neotropics. This project explored small-mammal carcass scavenging in a Neotropical, mid-elevation rainforest, and specifically studied the rate of carcass removal by scavengers, how the conspicuousness and weight of carcasses affect scavenging, and what vertebrate scavengers utilize this carrion resource. I deployed 194 mouse carcasses of various weights, above and below the leaf litter, and surveyed them daily until disappearance. I paired each carcass with a trail camera to help identify vertebrate scavengers. A general linear model analysis showed that most mouse carcasses disappeared within 1 to 2 days. Carcasses above the leaf litter were removed quicker and larger mice generally lasted longer. Only 6.25 % of the carcasses were removed by vertebrates. Most carcasses were removed by something too small to trigger the trail cameras, likely scarab beetles. The results of this study show that small-mammal carcasses are a sought-after resource in Neotropical forests, and that invertebrates are able to quickly hoard and secure small carrion more efficiently than vertebrate scavengers. A better understanding of scavenging ecology in Neotropical forests will help in developing a broader framework of the trophic interactions within and across ecosystems.